Performance Evaluation of Multiple Ultrasonographical Methods for the Detection of Primary Sjögren’s Syndrome - Xu, Shihao; Luo, Jing; Zhu, Chengwei; Jiang, Jiachun; Cheng, Hui; Wang, Ping; Hong, Jingwei; Fang, Jinxia; Pan, Jingjing; Brown, Matthew A.; Zhu, Xiaochun; Wang, Xiaobing (Frontiers in Immunology, 2021)
Major salivary gland ultrasonography (SGUS) is increasingly being recognized as having critical roles in differentiating primary Sjögren’s syndrome (pSS) from other connective tissue disorders. Contrast-enhanced ultrasonography (CEUS) has been reported to evaluate microvascularity of lesions in different tissues with objective angiographic index, eliminating the observer-dependent defect of ultrasonography. However, there are few relevant studies concentrating on the application of CEUS in the diagnosis and assessment for pSS, and their clinical utility prospect remains uncertain. In this study, a total of 227 eligible patients were enrolled, including 161 pSS and 66 non-pSS patients with comprehensive ultrasonographic evaluation of the parotid and submandibular glands, including grayscale ultrasonography, color Doppler sonography (CDS), and CEUS. Compared with non-pSS, pSS patients had significantly higher grayscale ultrasound (US) scores and CDS blood grades in the parotid gland and significantly higher grayscale US and CEUS scores in the submandibular glands. Diagnostic model combining ultrasonographic signatures, anti-SSA/Ro60, and keratoconjunctivitis sicca (KCS) tests showed a remarkable discrimination [mean area under the curve (AUC)0.963 in submandibular glands and 0.934 in parotid glands] for pSS, and the nomogram provided excellent prediction accuracy and good calibration in individualized prediction of pSS. A combination of multiple ultrasonographical examinations of the major salivary glands (SGs) is a promising technique that may be used as a practical alternative to minor SG biopsy in the detection of pSS.